متطلبات الإدارة الإلكترونية وأثرها في تحسين جودة الخدمات التعليمية من وجهة نظر أعضاء هيئة التدريس (دراسة ميدانية على كلية الاقتصاد بجامعة الزاوية) (Comprehensive Journal of Science, 2025)
This study aimed to identify the impact of e-management requirements (administrative, financial, security, technical, and human resources) on improving the quality of educational services from the perspective of faculty members at the University of Zawiya. To achieve the study's objectives and test its hypotheses, the researchers adopted a descriptive approach. The study included a simple random sample of (153) faculty members from the Faculty of Economics. Data was collected via a questionnaire and analyzed using the SPSS statistical software package. The results showed a statistically significant positive impact of e-management requirements (administrative, financial, security, technical, and human resources) on the quality of educational services, reflecting the importance of these requirements in enhancing the effectiveness of the educational process. The study also emphasized the importance of administrative, technical, human resources, financial, and security requirements in improving the quality of educational services, revealing a strong relationship, according to the respondents' answers, indicating that e-management requirements have an impact on improving the quality of educational services. Based on these results, the study recommends The study emphasizes the need to enhance investment in technological infrastructure and provide continuous training for faculty members to ensure their ability to use electronic systems efficiently. It also recommends developing security policies to protect sensitive data and information, and encouraging participation and interaction among all stakeholders, including administration and students, to ensure maximum benefit from e-governance in higher education institutions. These steps are considered essential to ensure a sustainable improvement in the quality of educational services and enhance the learning experience in the Faculty of Economics and all other educational institutions.